Dropped head related lamin A/C associated congenital muscular dystrophy case; previously defined as emerydreifuss muscular dystrophy - Tekin, Hande; Yılmaz, Sanem; Tekgül, Hasan; Gökben, Sarenur; Aktan, Gül (The Turkish Journal of Pediatrics, 2020)
Dropped head syndrome can be seen in many neuromuscular diseases. However, there are very few diseases in which neck extensors are weak among neuromuscular diseases. A 7 years old boy who had weakness of the neck extensor muscles, creatinine kinase elevation and dystrophy findings in biopsy followed up with the preliminary diagnosis of muscular dystrophy is presented. We detected p.N456K (c.1368C > A) heterozygote mutation by the gene sequencing in the Lamin A/C assocıated (LMNA) gene. This mutation was previously reported as Emery-Dreifuss muscular dystrophy.
Keywords: LMNA; congenital muscular dystrophy; dropped head